Synthesis and reactivity of a hypersilylsilylene - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Inorganic chemistry, 2019)
Stabilization of an amidinatosilylene with a bulky tris(trimethylsilyl)silyl substituent was realized with the preparation of PhC(NtBu)(2)Si{Si(SiMe3)(3)} (1) from PhC(NtBu)(2)SiHCl2 with K{Si(SiMe3)(3)} in more than 90% yield. The highly deshielded Si-29 NMR resonance (delta = 76.91 ppm) can be attributed to the absence of a pi-donating substituent. The molecular structure of 1 shows a trigonal-planar geometry around the Si-II center with a Si-II-Si-IV bond length of 2.4339(13) angstrom. A series of reactions of 1 with Me3NO, S, Se, and Te were performed. While siloxane derivatives (2 and 3) are obtained from reactions with Me3NO, silachalcogenones (4-6) are formed with other chalcogens. The presence of Si=E (E = S, Se, and Te) bonds in 4-6 have been confirmed by single crystal X-ray studies. Silaoxirane (7) formation was observed when 1 was treated with acetone, demonstrating the importance of the tris(trimethylsilyl)silyl group to kinetically and thermodynamically protect the silaoxirane derivative with less bulky substituents on the C atom.